Bimetallic Ni-Zn site anchored in siliceous zeolite framework for synergistically boosting propane dehydrogenation. (1st January 2022) - Huang, Chengming; Han, Dingmei; Guan, Linjie; Zhu, Linhua; Mei, Yi; He, Dedong; Zu, Yun
Graphical abstract: A highly stable bimetallic-sites catalyst of Ni-Zn anchored in the silicalite-1 zeolite framework is facilely fabricated by ligand-protected strategy, synergistically boosting propane dehydrogenation to propylene. Highlights: Bimetallic Ni-Zn site anchored in the silicalite-1 zeolitic framework are fabricated. Superior catalytic performance on the 0.2Ni0.06Zn-S-1 for PDH is achieved. High stability and activity of catalyst are remained after regeneration for 4 cycles. Synergistic effect between Ni-Zn sites favors propylene desorption to reduce coke deposition. Abstract: Propane dehydrogenation (PDH) is a prospective benign process for the production of propylene, but generally depends on high-price Pt and toxic Cr(VI) catalysts that often suffer from the rapid deactivation derived from metal sintering and severe coke deposition. To overcome these problems, the breakthroughs in an alternative catalyst design with efficient, low-cost and eco-friendly play a crucial role in successfully developing this process. Here, we facilely fabricate the bimetallic-site catalyst of Ni-Zn anchored in the zeolitic framework of silicalite-1 (depicted as NiZn-S-1) by employing ligand-protected strategy, which performs high temperature stability. Under comparable conditions, the NiZn-S-1 catalyst with high Ni/Zn molar ratio of 3:1 (named 0.2Ni0.06Zn-S-1) exhibits superior catalytic activity (initial propane conversion of 32.5 % and actual TOFpropane of 28.5 min −1 ) with low deactivation rate (0.0778 h −1 ) and great propylene selectivity (>90%) after 30 h on stream. In particular, the catalytic performance on this catalyst almost keeps same as that of fresh catalyst after 4 successive oxidation–reduction cycles. Multiple characterizations further demonstrate that the enhancement of PDH performance ought to be attributed to the synergistic effect between bimetallic Ni-Zn sites, which favors the selective activation of C–H bond and propylene desorption to reduce the formation of coke species with high graphitization degree, boosting the improvement of catalyst stability. The design of novel bimetallic-sites catalyst can give a new idea on the development of alternative PDH catalysts with economical- and environment-friendly in the future.